2021
DOI: 10.1249/mss.0000000000002620
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Engagement Worsens Health Outcomes and Limits Exercise Capacity in Growth-restricted Mice

Abstract: Introduction: A total of 161 million children a year are growth restricted, leading to a 47% increased risk of chronic disease in adulthood. Physical activity (PA) reduces the risk of mortality from chronic disease. The purpose of the present investigation was to determine the effect of a PA intervention (wheel running) on cardiac and skeletal muscle capacities in gestational (GUN) and postnatal (PUN) growth-restricted mice as compared with nonrestricted controls (CON). Methods: A low-protein cross-fostering F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Furthermore, Monica Hubal's research team demonstrated that variability can exists in the magnitude by which muscle responds (capacity to hypertrophy) to resistance exercise (49). Recently, Ferguson et al expanded on this work and demonstrated that healthy mice increase aerobic exercise capacity following wheel running while GR mice fail to improve exercise capacity and display signs of cardiac fibrosis (50). Potentially, during times of limited food availability epigenetic programming reduces resting metabolic rate to prolong survival.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Monica Hubal's research team demonstrated that variability can exists in the magnitude by which muscle responds (capacity to hypertrophy) to resistance exercise (49). Recently, Ferguson et al expanded on this work and demonstrated that healthy mice increase aerobic exercise capacity following wheel running while GR mice fail to improve exercise capacity and display signs of cardiac fibrosis (50). Potentially, during times of limited food availability epigenetic programming reduces resting metabolic rate to prolong survival.…”
Section: Discussionmentioning
confidence: 99%
“…The soleus was also excised, flash-frozen, and stored at −80°C. Both tissue samples were homogenized in C. Norris buffer (HEPES, B-glycerophosphate, ATP, protease inhibitor cocktail, benzamidine, PMSF, EDTA, MgCl 2 ) (14,17) and protein concentration determined utilizing a bicinchoninic acid assay. Equal concentrations of sample were loaded into a 12% polyacrylamide gel and separated by SDS-PAGE.…”
Section: Methodsmentioning
confidence: 99%
“…Although the changes in Casq1 and Drd1 would be beneficial during times of lower food availability, the alteration could be counterproductive once food sources are restored as what typically occurs as babies grow into adults (16). One such example of early life programming having an adverse adulthood health outcome was demonstrated by Ferguson et al (17) when the authors initially aimed to characterize the effects of physical activity (wheel running) on cardiovascular function in growth-restricted mice. Contrary to their initial hypothesis, postnatally growth-restricted mice had significantly reduced left ventricular volume and ventricular area leading to impairments in maximal exercise capacity.…”
mentioning
confidence: 99%